Negative pole piece, battery and electric device
By applying active layers with different thickness rates on the negative electrode current collector of the lithium-ion battery, the problem that existing lithium-ion batteries cannot take into account high charging rate, long cycle life and high energy density is solved, and efficient charging and long life of the battery are achieved.
Patent Information
- Application Number
- CN202411987634.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-29
AI Technical Summary
Existing lithium-ion batteries cannot take into account high charging rates, long cycle life and high energy density.
By coating the active layers with different thickness rates on the negative electrode current collector, the thickness ratio of the first active layer is controlled to be above 12%, and the thickness ratio of the second active layer to the nth active layer is below 12%, so as to adjust the thickness change and the porosity change of the active layer during the charging process.
It realizes the battery charging rate and cycle life while ensuring the battery energy density and capacity.
Smart Images

Figure CN119905518A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a negative electrode sheet, a battery and an electrical device. Background Art
[0002] Lithium-ion batteries are widely used in consumer batteries, power batteries and energy storage batteries due to their high operating voltage, high energy density and environmental friendliness. As people's quality of life improves, the requirements for the charging rate, cycle life and energy density of various electronic devices are getting higher and higher. However, existing lithium-ion batteries cannot take into account high charging rate, long cycle life and high energy density. Therefore, how to make batteries take into account high charging rate, long cycle life and high energy density has become an important research topic and also faces major challenges. Summary of the invention
[0003] In view of the problems existing in the background technology, the present invention provides a negative electrode plate, which can enable the battery to have a high charging rate, a long cycle life and a high energy density.
[0004] Specifically, the first aspect of the present invention provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode coating disposed on at least one side of the negative electrode current collector, wherein the negative electrode coating comprises: a first active layer close to the negative electrode current collector, a second active layer disposed on the first active layer, and so on, an nth active layer disposed on the n-1th active layer, where n is an integer from 2 to 5; the negative electrode active material in each active layer is graphite;
[0005] The thickness increase rate ΔT of the active layer decreases from the first active layer to the nth active layer, ΔT=(T 100%SOC -T 0% SOC )÷T 0% SOC , T 100% SOC Indicates the thickness of the active layer at 100% charge state, T 0% SOC represents the thickness of the active layer in the 0% charged state; and the thickness increase rate of the first active layer is greater than 12%, and the thickness increase rates of the second active layer to the nth active layer are all less than 12%.
[0006] The present invention coats active layers with different thickening rates on the negative electrode current collector, and controls the thickening rates of the active layers to decrease in sequence from the direction close to the negative electrode current collector to the direction far from the negative electrode current collector, and controls the thickening rate of the first active layer to be above 12%, and the thickening rates of the second active layer to the nth active layer to be below 12%, so that the active layer close to the upper layer of the negative electrode sheet obtains a smaller thickness change and a smaller porosity change during the charging process, thereby ensuring the energy density of the battery; at the same time, the active layer close to the lower layer obtains a larger thickness change and a larger porosity change, thereby generating an absorption effect on the electrolyte, and utilizing the convective mass transfer of the electrolyte to reduce the Li in the inner layer of the electrode dressing. + The diffusion polarization of the battery can be reduced, thereby improving the battery's charging rate and cycle life while ensuring the battery's energy density and capacity.
[0007] According to some embodiments of the present invention, n is 2, the thickness increase rate ΔT' of the first active layer is greater than the thickness increase rate ΔT", of the second active layer, ΔT'=(T' 100% SOC -T' 0% SOC )÷T' 0% SOC , T' 100% SOC represents the thickness of the first active layer at 100% charge state, T' 0% SOC represents the thickness of the first active layer at 0% charge state; ΔT" = (T" 100%SOC -T" 0% SOC )÷T” 0% SOC , T” 100% SOC represents the thickness of the second active layer at 100% charge state, T” 0% SOC represents the thickness of the second active layer at 0% charge state.
[0008] Optimizing the number of active layers helps reduce the difficulty of the production process, simplify the process, save production costs, and at the same time ensure the energy density and capacity of the battery and improve the battery's charging rate and cycle life.
[0009] According to some embodiments of the present invention, the thickness increase rate ΔT' of the first active layer is 12% to 18%; the thickness increase rate ΔT" of the second active layer is 6% to 12%; preferably, the thickness increase rate ΔT' of the first active layer is 15% to 18%; the thickness increase rate ΔT" of the second active layer is 6% to 10%.
[0010] The thickening rate affects the energy density and liquid absorption performance of the active layer. Optimizing the thickening rate within the scope of the present invention is beneficial to improving the charging rate and cycle life of the battery while ensuring the energy density and capacity of the battery.
[0011] According to some embodiments of the present invention, the raw materials of the first active layer include the first dispersant and the first binder, the raw materials of the second active layer include the second dispersant and the second binder, and so on, the raw materials of the nth active layer include the nth dispersant and the nth binder; the elastic modulus of the film formed by the first dispersant and the first binder is less than the elastic modulus of the film formed by the second dispersant and the second binder; and so on, the elastic modulus of the film formed by the n-1th dispersant and the n-1th binder is less than the elastic modulus of the film formed by the nth dispersant and the nth binder. The elastic modulus affects the thickening rate of the active layer to a certain extent, and thus affects the thickness change and porosity change of the active layer during the charging process.
[0012] According to some embodiments of the present invention, n is 2; the mass ratio of the first dispersant and the first binder is (0.1-1.2): (1.8-3.8); the total mass proportion of the first dispersant and the first binder in the raw material of the first active layer is 1.9%-5.0%; the elastic modulus of the film formed by the first dispersant and the first binder is 10MPa-50MPa; the mass ratio of the second dispersant and the second binder is (0.3-1.4): (0.2-2.3); the mass proportion of the second dispersant and the second binder in the raw material of the second active layer is 0.5%-3.7%; the elastic modulus of the film formed by the second dispersant and the second binder is 55MPa-100MPa. The amount and proportion of the dispersant and the binder affect the elastic modulus, and the elastic modulus affects the thickening rate of the active layer to a certain extent. By optimizing the amount and proportion of the dispersant and the binder, it is beneficial to further improve the charging rate and cycle life of the battery while ensuring the energy density and capacity of the battery.
[0013] According to some embodiments of the present invention, the mass ratio of the first dispersant and the first binder is (1-1.2):(2-3); the total mass proportion of the first dispersant and the first binder in the raw materials of the first active layer is 3%-4.2%; the elastic modulus of the film formed by the first dispersant and the first binder is 10MPa-20MPa; the mass ratio of the second dispersant and the second binder is (0.3-0.7):(1.3-2.3); the mass proportion of the second dispersant and the second binder in the raw materials of the second active layer is 1.6%-3.0%; the elastic modulus of the film formed by the second dispersant and the second binder is 60MPa-80MPa.
[0014] According to some embodiments of the present invention, the first binder, the second binder, and so on to the nth binder each include one or more of styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol, sodium alginate, polymethacrylic acid, and carboxymethyl chitosan. The first dispersant, the second dispersant, and so on to the nth dispersant each include one or more of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose.
[0015] According to some embodiments of the present invention, n is 2, and the raw materials of the first active layer include graphite, a first conductive agent, a first dispersant, and a first binder; the mass ratio of graphite, the first conductive agent, the first dispersant, and the first binder is (93.4-97.4): (0.3-1.6): (0.1-1.2): (1.8-3.8); the raw materials of the second active layer include graphite, a second conductive agent, a second dispersant, and a second binder; the mass ratio of graphite, the second conductive agent, the second dispersant, and the second binder is (96.6-98.9): (0-0.8): (0.3-1.4): (0.2-2.3). Optimizing the ratio of the raw materials in the active layer is conducive to controlling the thickening rate of the active layer.
[0016] The second aspect of the present invention provides a battery, comprising the negative electrode sheet of the first aspect of the present invention. Due to the use of the negative electrode sheet of the first aspect of the present invention, the battery of the present invention can have high charging rate, long cycle life and high energy density.
[0017] The third aspect of the present invention provides an electric device, comprising the battery of the second aspect of the present invention. Since the negative electrode sheet of the first aspect of the present invention is used, the electric device of the present invention also has the advantages of high charging rate, long cycle life and high energy density.
[0018] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0020] Figure 1 It is a schematic diagram of the structure of the negative electrode plate of an embodiment of the present invention.
[0021] Figure 2 It is a cross-sectional scanning electron microscope (SEM) image of each negative electrode sheet at 0% SOC and 100% SOC.
[0022] Figure 3It is a comparison chart of the equivalent 4.5C cycle performance of the batteries corresponding to Examples 1-3 and Comparative Examples 1-3.
[0023] Reference numerals:
[0024] 100, negative electrode current collector; 200, first active layer; 300, second active layer. DETAILED DESCRIPTION
[0025] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0026] In the description of the present invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, "multiple" means at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0027] Lithium-ion batteries are widely used in consumer batteries, power batteries and energy storage batteries due to their high operating voltage, high energy density and environmental friendliness. As people's quality of life improves, the requirements for the charging rate, cycle life and energy density of various electronic devices are getting higher and higher. However, existing lithium-ion batteries cannot take into account high charging rate, long cycle life and high energy density. Therefore, how to make batteries take into account high charging rate, long cycle life and high energy density has become an important research topic.
[0028] Research has found that the porosity of the coating on the negative electrode sheet changes during the entire fast charging process. Designing only based on the initial porosity of the negative electrode coating to improve the battery's charging rate, cycle life and other performance will not achieve the expected results.
[0029] In order to solve the above problems, the present invention provides a negative electrode plate, by coating active layers with different thickening rates on the negative electrode current collector, and controlling the thickening rate of the active layer to decrease in sequence from close to the negative electrode current collector to far away from the negative electrode current collector, and controlling the thickening rate of the first active layer to be above 12%, and the thickening rates of the second active layer to the nth active layer to be below 12%, so that the negative electrode plate obtains a smaller thickness change and porosity change in the upper active layer during charging, thereby ensuring the energy density of the battery; at the same time, the lower active layer obtains a larger thickness change and porosity change, resulting in absorption of the electrolyte, and utilizing the convection mass transfer of the electrolyte to reduce the Li in the inner layer of the electrode dressing.+ The diffusion polarization of the battery can be reduced, thereby improving the battery's charging rate and cycle life while ensuring the battery's energy density and capacity.
[0030] Specifically, the first aspect of the present invention provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode coating disposed on at least one side of the negative electrode current collector, wherein the negative electrode coating comprises: a first active layer close to the negative electrode current collector, a second active layer disposed on the first active layer, and so on, an nth active layer disposed on the n-1th active layer, where n is an integer from 2 to 5; the negative electrode active material in each active layer is graphite;
[0031] The thickness increase rate ΔT of the active layer decreases from the first active layer to the nth active layer, ΔT=(T 100%SOC -T 0% SOC )÷T 0% SOC , T 100% SOC Indicates the thickness of the active layer at 100% charge state, T 0% SOC represents the thickness of the active layer in the 0% charged state; and the thickness increase rate of the first active layer is greater than 12%, and the thickness increase rates of the second active layer to the nth active layer are all less than 12%.
[0032] In this paper, T 100% SOC Indicates the thickness of the active layer at 100% charge state, T 0% SOC Indicates the thickness of the active layer at 0% charge state. For example, for a certain active layer, T 100% SOC It represents the thickness of the active layer at 100% charge state (i.e. fully charged state), T 0% SOC It indicates the thickness of the active layer at 0% charge state (i.e., the state of complete discharge after full charge). The thickness increase rate of the first active layer is greater than that of the second active layer, the thickness increase rate of the second active layer is greater than that of the third active layer, and so on. The thickness increase rate of the n-1th active layer is greater than that of the nth active layer.
[0033] In some embodiments, n is 2, the thickness increase rate ΔT' of the first active layer is greater than the thickness increase rate ΔT", of the second active layer, ΔT'=(T' 100% SOC -T' 0% SOC )÷T' 0% SOC , T' 100% SOCrepresents the thickness of the first active layer at 100% charge state, T' 0% SOC represents the thickness of the first active layer at 0% charge state; ΔT" = (T" 100% SOC -T" 0%SOC )÷T” 0% SOC , T” 100% SOC represents the thickness of the second active layer at 100% charge state, T” 0% SOC Indicates the thickness of the second active layer at 0% charge state. Optimizing the number of active layers is conducive to simplifying the process, reducing the difficulty of the production process, saving production costs, while ensuring the energy density and capacity of the battery and improving the charging rate and cycle life of the battery.
[0034] In some embodiments, the thickness increase rate ΔT' of the first active layer is 12% to 18%; the thickness increase rate ΔT" of the second active layer is 6% to 12%. The thickness increase rate affects the energy density and liquid absorption performance of the active layer. Optimizing the thickness increase rate within the scope of the present invention is beneficial to improving the charging rate and cycle life of the battery while ensuring the energy density and capacity of the battery.
[0035] In some specific embodiments, the thickness increase rate ΔT' of the first active layer is 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%.
[0036] In some specific embodiments, the thickness increase rate ΔT" of the second active layer is 6%, 7%, 8%, 9%, 10%, 11% or 12%.
[0037] In some specific embodiments, the thickness increase rate ΔT' of the first active layer is 15% to 18%; the thickness increase rate ΔT" of the second active layer is 6% to 10%.
[0038] In some embodiments, the raw materials of the first active layer include a first dispersant and a first binder, the raw materials of the second active layer include a second dispersant and a second binder, and so on, the raw materials of the nth active layer include an nth dispersant and an nth binder. The elastic modulus of the film formed by the first dispersant and the first binder is smaller than the elastic modulus of the film formed by the second dispersant and the second binder; and so on, the elastic modulus of the film formed by the n-1th dispersant and the n-1th binder is smaller than the elastic modulus of the film formed by the nth dispersant and the nth binder. The elastic modulus affects the thickening rate of the active layer to a certain extent, and then affects the thickness change and porosity change of the active layer during the charging process. The smaller the elastic modulus, the greater the thickness change and porosity change of the active layer during the charging process; and vice versa.
[0039] In this article, the adhesive film refers to a film formed by mixing and drying the dispersant and the binder. The drying includes drying in the shade at room temperature and then baking at 75°C-85°C for 1.5h-2.5h.
[0040] In some embodiments, n is 2. The mass ratio of the first dispersant and the first binder is (0.1-1.2): (1.8-3.8). The total mass proportion of the first dispersant and the first binder in the raw material of the first active layer is 1.9%-5.0%. The elastic modulus of the film formed by the first dispersant and the first binder is 10MPa-50MPa. The mass ratio of the second dispersant and the second binder is (0.3-1.4): (0.2-2.3). The mass proportion of the second dispersant and the second binder in the raw material of the second active layer is 0.5%-3.7%. The elastic modulus of the film formed by the second dispersant and the second binder is 55MPa-100MPa. The amount and proportion of the dispersant and the binder affect the elastic modulus, and the elastic modulus affects the thickening rate of the active layer to a certain extent. By optimizing the amount and proportion of the dispersant and the binder, it is beneficial to further improve the charging rate and cycle life of the battery while ensuring the energy density and capacity of the battery.
[0041] In some embodiments, the mass ratio of the first dispersant to the first binder is (1-1.2):(2-3). The total mass proportion of the first dispersant and the first binder in the raw material of the first active layer is 3%-4.2%. The elastic modulus of the film formed by the first dispersant and the first binder is 10MPa-20MPa. The mass ratio of the second dispersant and the second binder is (0.3-0.7):(1.3-2.3). The mass proportion of the second dispersant and the second binder in the raw material of the second active layer is 1.6%-3.0%. The elastic modulus of the film formed by the second dispersant and the second binder is 60MPa-80MPa.
[0042] In some specific embodiments, the mass ratio of the first dispersant to the first binder is 1:2, 1:2.2, 1:2.4, 1:2.6, 1:2.8, 1:3, 1.1:2, 1.1:2.2, 1.1:2.4, 1.1:2.6, 1.1:2.8, 1.1:3, 1.2:2, 1.2:2.2, 1.2:2.4, 1.2:2.6, 1.2:2.8 or 1.2:3.
[0043] In some specific embodiments, the total mass percentage of the first dispersant and the first binder in the raw material of the first active layer is 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4.0% or 4.2%.
[0044] In some specific embodiments, the elastic modulus of the adhesive film formed by the first dispersant and the first binder is 10 MPa, 12 MPa, 14 MPa, 16 MPa, 18 MPa or 20 MPa.
[0045] In some specific embodiments, the mass ratio of the second dispersant to the second binder is 0.3:1.3, 0.3:1.5, 0.3:1.7, 0.3:1.9, 0.3:2.1, 0.3:2.3, 0.4:1.3, 0.4:1.5, 0.4:1.7, 0.4:1.9, 0.4:2.1, 0.4:2.3, 0.5:1.3, 0.5:2.1, 0.5:2.3, 0.5:1.3, 0.5:2.1 :1.5, 0.5:1.7, 0.5:1.9, 0.5:2.1, 0.5:2.3, 0.6:1.3, 0.6:1.5, 0.6:1.7, 0.6:1.9, 0.6:2.1, 0.6:2.3, 0.7:1.3, 0.7:1.5, 0.7:1.7, 0.7:1.9, 0.7:2.1 or 0.7:2.3.
[0046] In some specific embodiments, the mass proportion of the second dispersant and the second binder in the raw material of the second active layer is 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8% or 3.0%.
[0047] In some specific embodiments, the elastic modulus of the adhesive film formed by the second dispersant and the second binder is 60 MPa, 65 MPa, 70 MPa, 75 MPa or 80 MPa.
[0048] In some embodiments, the mass proportion of the first binder in the raw material of the first active layer is 1.8%-3.8%; the mass proportion of the second binder in the raw material of the second active layer is 0.2%-2.3%. The amount of binder affects the thickening rate of the active layer to a certain extent. Optimizing the amount of binder is conducive to controlling the thickness change of the active layer during charging, while ensuring the energy density and capacity of the battery, further improving the charging rate and cycle life of the battery.
[0049] In this article, the raw materials of the active layer refer to the raw materials present in the active layer of the final negative electrode sheet product, such as graphite, conductive agent, dispersant, binder, etc., excluding the solvent used in preparing the negative electrode slurry. The mass proportion of the binder in the raw materials of the active layer refers to the ratio of the mass of the binder to the total mass of the raw materials of the active layer.
[0050] In some specific embodiments, the mass proportion of the first binder in the raw material of the first active layer is 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6% or 3.8%.
[0051] In some specific embodiments, the mass proportion of the second binder in the raw material of the second active layer is 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2%, 2.1%, 2.2% or 2.3%.
[0052] In some embodiments, the first binder, the second binder and the nth binder each include one or more of styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol, sodium alginate, polymethacrylic acid and carboxymethyl chitosan.
[0053] In some specific embodiments, the first binder, the second binder, and the nth binder each include styrene-butadiene rubber and polyacrylic acid.
[0054] In some embodiments, the first dispersant, the second dispersant, and so on to the nth dispersant each include one or more of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose.
[0055] In some specific embodiments, the first dispersant, the second dispersant, and so on to the nth dispersant each include one or more of sodium carboxymethyl cellulose 500, sodium carboxymethyl cellulose 350, sodium carboxymethyl cellulose 2300, and lithium carboxymethyl cellulose 500.
[0056] In some embodiments, n is 2, and the raw materials of the first active layer include graphite, a first conductive agent, a first dispersant, and a first binder; the mass ratio of graphite, the first conductive agent, the first dispersant, and the first binder is (93.4-97.4): (0.3-1.6): (0.1-1.2): (1.8-3.8); the raw materials of the second active layer include graphite, a second conductive agent, a second dispersant, and a second binder; the mass ratio of graphite, the second conductive agent, the second dispersant, and the second binder is (96.6-98.9): (0-0.8): (0.3-1.4): (0.2-2.3). Optimizing the ratio of the raw materials in the active layer is beneficial to controlling the thickening rate of the active layer.
[0057] In some specific embodiments, the mass ratio of graphite, the first conductive agent, the first dispersant and the first binder is, for example, (95-97):(0.3-1.0):(1-1.2):(2-3).
[0058] In some specific embodiments, the mass ratio of graphite, the second conductive agent, the second dispersant, and the second binder is, for example, (96.6-98):(0.3-0.8):(0.3-0.7):(1.3-2.3).
[0059] In some embodiments, the graphite includes one or more of natural graphite, modified natural graphite, and artificial graphite.
[0060] In some specific embodiments, the D50 particle size of the graphite in the first active layer is 12 to 18 microns, for example, 12 microns, 13 microns, 14 microns, 15 microns, 16 microns, 17 microns or 18 microns. The D90 particle size of the graphite in the first active layer is 25 to 30 microns, for example, 25 microns, 26 microns, 27 microns, 28 microns, 29 microns or 30 microns. The D50 particle size of the graphite in the second active layer is 10 to 15 microns, for example, 10 microns, 11 microns, 12 microns, 13 microns, 14 microns, 15 microns. The D90 particle size of the graphite in the second active layer is 20 to 25 microns, for example, 20 microns, 21 microns, 22 microns, 23 microns, 24 microns or 25 microns.
[0061] In some embodiments, the conductive agent in each active layer includes one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0062] In some embodiments, the gram capacity of the first active layer is 352-380 mAh / g, such as 352 mAh / g, 360 mAh / g, 370 mAh / g or 380 mAh / g. The gram capacity of the second active layer is 340-370 mAh / g, such as 340 mAh / g, 350 mAh / g, 360 mAh / g or 370 mAh / g.
[0063] In some embodiments, the thickness ratio of the second active layer to the first active layer may be 1:(0.1-9), for example, 1:0.1, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8 or 1:9.
[0064] In some embodiments, the first active layer slurry is coated on both surfaces of the negative electrode current collector, and the first active layer is formed after rolling, and then the second active layer slurry is coated on the surface of the first active layer, and the second active layer is formed after rolling, so as to obtain a double-sided double-layer coated negative electrode sheet. After baking, the double-sided surface density of the negative electrode sheet is 250-350g / m 2 .
[0065] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0066] Example 1
[0067] (1) Graphite, conductive carbon black (SP), and sodium carboxymethyl cellulose (CMC) were mixed in proportion; then polyacrylic acid (PAA), water, and styrene-butadiene rubber (SBR) were added in proportion and mixed to obtain the first active layer slurry, the solid content of the slurry was 52%, and the mass ratio of graphite, SP, CMC, PAA, and SBR was 96.2:0.3:1.2:0.5:1.8. Among them, CMC, PAA, and SBR were mixed in a mass ratio of 1.2:0.5:1.8 and poured into a 5mm deep mold, dried in the shade at room temperature for 5 days, and then baked at 80°C for 2h to form a film, which was trimmed into 10mm*100mm long strips and tested for elastic modulus using a universal tensile machine. The elastic modulus of the tested film was 10MPa.
[0068] (2) Graphite, SP, and CMC are mixed uniformly in proportion; then PAA, water, and SBR are added thereto in proportion and mixed thoroughly to obtain a second active layer slurry, wherein the slurry has a solid content of 55%, and the mass ratio of graphite, SP, CMC, PAA, and SBR is 96.8:0.8:0.3:1.6:0.5. Among them, according to the method of step 1, CMC, PAA, and SBR are mixed in a mass ratio of 0.3:1.6:0.5 and then dried to obtain a film, and the elastic modulus of the film is tested according to the method of step 1 and is 80 MPa.
[0069] (3) The first active layer slurry and the second active layer slurry are coated on one side of the negative electrode current collector 100 by a double-layer coating die head of a coating machine to form a first active layer 200 and a second active layer 300 on one side of the negative electrode current collector; after baking, the first active layer slurry and the second active layer slurry are coated on the other side of the negative electrode current collector 100 to form a first active layer 200 and a second active layer 300 on the other side of the negative electrode current collector. After baking, the negative electrode sheet is obtained by rolling. The total thickness of the first active layer 200 and the second active layer 300 on the negative electrode sheet is 63 μm. Figure 1 shown.
[0070] Example 2
[0071] (1) Graphite, SP, and CMC are mixed in proportion and then PAA, water, and SBR are added in proportion and mixed to obtain a first active layer slurry, wherein the slurry has a solid content of 52% and the mass ratio of graphite, SP, CMC, PAA, and SBR is 96.1:0.3:1.1:0.7:1.8. According to the method of step 1 of Example 1, CMC, PAA, and SBR are mixed in a mass ratio of 1.1:0.7:1.8 and dried to obtain a film, and the elastic modulus of the film is tested according to the method of step 1 of Example 1 and is 20 MPa.
[0072] (2) Graphite, SP, and CMC were mixed in proportion and then PAA, water, and SBR were added in proportion and mixed to obtain a second active layer slurry, wherein the slurry had a solid content of 55%, and the mass ratio of graphite, SP, CMC, PAA, and SBR was 96.8:0.8:0.3:1.6:0.5. Among them, CMC, PAA, and SBR were mixed in a mass ratio of 0.3:1.6:0.5 and then dried to obtain a film, and the elastic modulus of the film was tested according to the method of step 1 of Example 1 and was 80 MPa.
[0073] (3) The first active layer slurry and the second active layer slurry are coated on one side of the negative electrode current collector 100 by a double-layer coating die head of a coating machine to form a first active layer 200 and a second active layer 300 on one side of the negative electrode current collector; after baking, the first active layer slurry and the second active layer slurry are coated on the other side of the negative electrode current collector 100 to form a first active layer 200 and a second active layer 300 on the other side of the negative electrode current collector. After baking, the negative electrode sheet is obtained by rolling. The total thickness of the first active layer 200 and the second active layer 300 on the negative electrode sheet is 63 μm. Figure 1 shown.
[0074] Example 3
[0075] (1) Graphite, SP, and CMC are mixed in proportion and then PAA, water, and SBR are added in proportion and mixed to obtain a first active layer slurry, wherein the slurry has a solid content of 52% and the mass ratio of graphite, SP, CMC, PAA, and SBR is 96.1:0.3:1.1:0.7:1.8. According to the method of step 1 of Example 1, CMC, PAA, and SBR are mixed in a mass ratio of 1.1:0.7:1.8 and dried to obtain a film, and the elastic modulus of the film is tested according to the method of step 1 of Example 1 and is 20 MPa.
[0076] (2) Graphite, SP, and CMC were mixed uniformly in proportion; then PAA, water, and SBR were added thereto in proportion and mixed thoroughly to obtain a second active layer slurry, wherein the slurry had a solid content of 55%, and the mass ratio of graphite, SP, CMC, PAA, and SBR was 97.1:0.8:0.3:1.4:0.4. According to the method of step 1 of Example 1, CMC, PAA, and SBR were mixed in a mass ratio of 0.3:1.4:0.4 and then dried to obtain a film, and the elastic modulus of the film was tested according to the method of step 1 of Example 1 to be 60 MPa.
[0077] (3) The first active layer slurry and the second active layer slurry are coated on one side of the negative electrode current collector 100 by a double-layer coating die head of a coating machine to form a first active layer 200 and a second active layer 300 on one side of the negative electrode current collector; after baking, the first active layer slurry and the second active layer slurry are coated on the other side of the negative electrode current collector 100 to form a first active layer 200 and a second active layer 300 on the other side of the negative electrode current collector. After baking, the negative electrode sheet is obtained by rolling. The total thickness of the first active layer 200 and the second active layer 300 on the negative electrode sheet is 63 μm. Figure 1 shown.
[0078] Example 4
[0079] The negative electrode sheet was prepared according to the method of Example 1, except that, in step 1, the mass ratio of graphite, SP, CMC, PAA and SBR was 95.8:0.3:1.2:0.8:1.9. According to the method of step 1 of Example 1, CMC, PAA and SBR in a mass ratio of 1.2:0.8:1.9 were mixed and dried to obtain a film, and the elastic modulus of the film tested according to the method of step 1 of Example 1 was 25 MPa. In step 2, the mass ratio of graphite, SP, CMC, PAA and SBR was 96.8:0.8:0.3:1.6:0.5. According to the method of step 1 of Example 1, CMC, PAA and SBR in a mass ratio of 0.3:1.6:0.5 were mixed and dried to obtain a film, and the elastic modulus of the film tested according to the method of step 1 of Example 1 was 80 MPa.
[0080] Example 5
[0081] The negative electrode sheet was prepared according to the method of Example 1, except that, in step 1, the mass ratio of graphite, SP, CMC, PAA and SBR was 96.5:0.3:1.2:0.2:1.8. According to the method of step 1 of Example 1, CMC, PAA and SBR in a mass ratio of 1.2:0.2:1.8 were mixed and dried to obtain a film, and the elastic modulus of the film tested according to the method of step 1 of Example 1 was 8MPa. In step 2, the mass ratio of graphite, SP, CMC, PAA and SBR was 96.8:0.8:0.3:1.6:0.5. According to the method of step 1 of Example 1, CMC, PAA and SBR in a mass ratio of 0.3:1.6:0.5 were mixed and dried to obtain a film, and the elastic modulus of the film tested according to the method of step 1 of Example 1 was 80MPa.
[0082] Example 6
[0083] The negative electrode sheet was prepared according to the method of Example 1, except that, in step 1, the mass ratio of graphite, SP, CMC, PAA and SBR was 96.2:0.3:1.2:0.5:1.8. According to the method of step 1 of Example 1, CMC, PAA and SBR in a mass ratio of 1.2:0.5:1.8 were mixed and dried to obtain a film, and the elastic modulus of the film tested according to the method of step 1 of Example 1 was 10 MPa. In step 2, the mass ratio of graphite, SP, CMC, PAA and SBR was 97.7:0.3:0.7:0.9:0.4. According to the method of step 1 of Example 1, CMC, PAA and SBR in a mass ratio of 0.7:0.9:0.4 were mixed and dried to obtain a film, and the elastic modulus of the film tested according to the method of step 1 of Example 1 was 25 MPa.
[0084] Example 7
[0085] The negative electrode sheet was prepared according to the method of Example 1, except that, in step 1, the mass ratio of graphite, SP, CMC, PAA and SBR was 96.2:0.3:1.2:0.5:1.8. According to the method of step 1 of Example 1, CMC, PAA and SBR in a mass ratio of 1.2:0.5:1.8 were mixed and dried to obtain a film, and the elastic modulus of the film tested according to the method of step 1 of Example 1 was 10 MPa. In step 2, the mass ratio of graphite, SP, CMC, PAA and SBR was 96.6:0.8:0.3:1.8:0.5. According to the method of step 1 of Example 1, CMC, PAA and SBR in a mass ratio of 0.3:1.8:0.5 were mixed and dried to obtain a film, and the elastic modulus of the film tested according to the method of step 1 of Example 1 was 85 MPa.
[0086] Comparative Example 1
[0087] (1) Graphite, SP, and CMC are mixed in proportion and then PAA, water, and SBR are added in proportion and mixed to obtain a first active layer slurry, wherein the slurry has a solid content of 52% and the mass ratio of graphite, SP, CMC, PAA, and SBR is 96.2:0.3:1.2:0.5:1.8. According to the method of step 1 of Example 1, CMC, PAA, and SBR are mixed in a mass ratio of 1.2:0.5:1.8 and dried to obtain a film, and the elastic modulus of the film is tested according to the method of step 1 of Example 1 to be 10 MPa.
[0088] (2) Graphite, SP, and CMC are mixed in proportion and then PAA, water, and SBR are added in proportion and mixed to obtain a second active layer slurry, wherein the solid content of the slurry is 55%, and the mass ratio of graphite, SP, CMC, PAA, and SBR is 96.2:0.3:1.2:0.5:1.8. According to the method of step 1 of Example 1, CMC, PAA, and SBR are mixed in a mass ratio of 1.2:0.5:1.8 and dried to obtain a film, and the elastic modulus of the film is tested according to the method of step 1 of Example 1 to be 10 MPa.
[0089] (3) The first active layer slurry and the second active layer slurry are coated on one side of the negative electrode current collector by a double-layer coating die head of a coating machine to form the first active layer and the second active layer on the surface of one side of the negative electrode current collector; after baking, the first active layer slurry and the second active layer slurry are coated on the other side of the negative electrode current collector to form the first active layer and the second active layer on the surface of the other side of the negative electrode current collector; after baking, the negative electrode sheet is obtained by rolling. The total thickness of the first active layer and the second active layer on the negative electrode sheet is 63 μm.
[0090] Comparative Example 2
[0091] (1) Graphite, SP, and CMC are mixed in proportion and then PAA, water, and SBR are added in proportion and mixed to obtain a first active layer slurry, wherein the slurry has a solid content of 52% and the mass ratio of graphite, SP, CMC, PAA, and SBR is 96.3:0.3:0.4:1.2:1.8. According to the method of step 1 of Example 1, CMC, PAA, and SBR are mixed in a mass ratio of 0.4:1.2:1.8 and dried to obtain a film, and the elastic modulus of the film is tested according to the method of step 1 of Example 1 and is 40 MPa.
[0092] (2) Graphite, SP, and CMC were mixed uniformly in proportion; then PAA, water, and SBR were added thereto in proportion and mixed thoroughly to obtain a second active layer slurry, wherein the slurry had a solid content of 55%, and the mass ratio of graphite, SP, CMC, PAA, and SBR was 96.1:0.3:1.1:0.7:1.8. According to the method of step 1 of Example 1, CMC, PAA, and SBR were mixed in a mass ratio of 1.1:0.7:1.8 and then dried to obtain a film, and the elastic modulus of the film was tested according to the method of step 1 of Example 1 to be 20 MPa.
[0093] (3) The first active layer slurry and the second active layer slurry are coated on one side of the negative electrode current collector by a double-layer coating die head of a coating machine to form the first active layer and the second active layer on the surface of one side of the negative electrode current collector; after baking, the first active layer slurry and the second active layer slurry are coated on the other side of the negative electrode current collector to form the first active layer and the second active layer on the surface of the other side of the negative electrode current collector; after baking, the negative electrode sheet is obtained by rolling. The total thickness of the first active layer and the second active layer on the negative electrode sheet is 63 μm.
[0094] Comparative Example 3
[0095] (1) Graphite, SP, and CMC are mixed uniformly in proportion; then PAA, water, and SBR are added thereto in proportion and mixed thoroughly to obtain a first active layer slurry, wherein the slurry has a solid content of 52%, and the mass ratio of graphite, SP, CMC, PAA, and SBR is 96.8:0.8:0.3:1.6:0.5. According to the method of step 1 of Example 1, CMC, PAA, and SBR are mixed in a mass ratio of 0.3:1.6:0.5 and then dried to obtain a film, and the elastic modulus of the film is tested according to the method of step 1 of Example 1 to be 80 MPa.
[0096] (2) Graphite, SP, and CMC were mixed uniformly in proportion; then PAA, water, and SBR were added thereto in proportion and mixed thoroughly to obtain a second active layer slurry, wherein the slurry had a solid content of 55%, and the mass ratio of graphite, SP, CMC, PAA, and SBR was 96.1:0.3:1.1:0.7:1.8. According to the method of step 1 of Example 1, CMC, PAA, and SBR were mixed in a mass ratio of 1.1:0.7:1.8 and then dried to obtain a film, and the elastic modulus of the film was tested according to the method of step 1 of Example 1 to be 20 MPa.
[0097] (3) The first active layer slurry and the second active layer slurry are coated on one side of the negative electrode current collector by a double-layer coating die head of a coating machine to form the first active layer and the second active layer on the surface of one side of the negative electrode current collector; after baking, the first active layer slurry and the second active layer slurry are coated on the other side of the negative electrode current collector to form the first active layer and the second active layer on the surface of the other side of the negative electrode current collector; after baking, the negative electrode sheet is obtained by rolling. The total thickness of the first active layer and the second active layer on the negative electrode sheet is 63 μm.
[0098] Using the negative electrode sheets prepared in Examples 1-7 and Comparative Examples 1-3, batteries were prepared according to the following general method.
[0099] (1) Preparation method of positive electrode sheet: polyvinylidene fluoride (PVDF) binder is dissolved in N-methylpyrrolidone (NMP) solvent, and the solution is fully stirred to form a clear solution; conductive carbon black (SP) and lithium iron phosphate (LFP) active material are added to the clear solution, wherein the mass ratio of LFP, SP and PVDF is 8:1:1, and the solution is stirred evenly to obtain a slurry with a certain fluidity, and the slurry is coated on both sides of a 13 μm thick metal aluminum foil, dried to obtain a positive electrode sheet, and then cold pressed and slit), and then a positive electrode tab made of a 0.1 mm thick tab aluminum strip is welded to the aluminum foil to obtain a positive electrode sheet.
[0100] (2) The prepared negative electrode sheet, positive electrode sheet and isolation membrane are stacked to form a battery cell, and then the battery cell is placed in a battery aluminum-plastic film, and the electrolyte is injected into it. The soft-pack battery is then produced through processes such as formation and capacity division.
[0101] Test thickening rate:
[0102] (1) Testing the thickness increase rate of the first active layer
[0103] Prepare the first active layer slurry according to the method of step 1 of Example 1; apply the first active layer slurry on the surface of the negative electrode current collector by a coating machine, bake and roll to obtain a negative electrode plate, wherein the thickness of the first active layer is the same as the total thickness of the first active layer and the second active layer in the negative electrode plate prepared in Example 1, which is 63 μm. Assemble the negative electrode plates into two lithium-ion batteries according to the general method above. After the chemical composition and capacity division process, adjust the SOC of the two batteries to 0% (i.e., discharge to 0% SOC after being fully charged) and 100% with the same current, and disassemble the negative electrode plates with the corresponding SOC in an environment with a dew point of -40°C, and measure the thickness of the first active layer of the negative electrode plate at 0% charge state, which is recorded as T' 0% SOC . Measure the thickness of the first active layer of the negative electrode sheet at 100% charge state, recorded as T' 100% SOC According to the formula ΔT'=(T' 100%SOC -T' 0% SOC )÷T' 0%SOC Calculate the thickness increase rate of the first active layer.
[0104] The test method for the thickness increase rate of the first active layer in other embodiments and comparative examples is the same as described above. The test results are shown in Table 1 below.
[0105] (2) Testing the thickness increase rate of the second active layer
[0106] Prepare the second active layer slurry according to the method of step 2 of Example 1; apply the second active layer slurry on the surface of the negative electrode current collector by a coating machine, bake and roll to obtain a negative electrode plate, wherein the thickness of the second active layer is the same as the total thickness of the first active layer and the second active layer in the negative electrode plate prepared in Example 1, which is 63μm. Assemble the negative electrode plates into two lithium-ion batteries according to the general method above. After the chemical composition and capacity division process, adjust the SOC of the two batteries to 0% (i.e., discharge to 0% SOC after being fully charged) and 100% (the charging conditions are the same as the charging conditions for testing the thickening rate of the first active layer) with the same current, disassemble the negative electrode plates corresponding to the SOC in an environment with a dew point of -40°C, and measure the thickness of the second active layer of the lithium-ion battery at 0% charge state, recorded as T" 0% SOC . And measure the thickness of the second active layer at 100% charge state, record it as T” 100% SOC , according to the formula ΔT”=(T” 100% SOC -T" 0% SOC )÷T” 0% SOC Calculate the thickness increase rate of the second active layer.
[0107] The test method for the thickness increase rate of the second active layer in other embodiments and comparative examples is the same as described above. The test results are shown in Table 1 below.
[0108] It should be pointed out that the thickening rate of the active layer has nothing to do with the thickness of the active layer itself. In order to facilitate the testing of the thickening rates of the first active layer and the second active layer in the negative electrode sheets prepared in the embodiments and comparative examples, as described above, the present invention separately applies the first active layer slurry and the second active layer slurry on the surface of the negative electrode collector to form different negative electrode sheets and assembles them into batteries respectively. The thickening rates of the first and second active layers are obtained through separate testing. Theoretically, the results of directly testing the thickening rates of the first and second active layers in the double-layer coated negative electrode sheets prepared in the embodiments and comparative examples are consistent with the results obtained through the separate tests above. To verify this point, taking Example 1 as an example, Figure 2 , Figure 2a and 2a' are SEM cross-sectional images of the negative electrode sheet at 0% SOC and 100% SOC obtained according to the method for testing the thickness increase rate of the first active layer in (1) above, T' 0% SOC 63μm( Figure 2 a), T' 100% SOC 74μm( Figure 2 a'). Figure 2 b and 2b' are SEM cross-sectional images of the negative electrode sheet at 0% SOC and 100% SOC obtained according to the method for testing the thickness increase rate of the second active layer in (2) above, T' 0% SOC 63μm( Figure 2 b), T' 100% SOC 66μm( Figure 2 b'). Figure 2 c and 2c' are SEM cross-sectional images of the negative electrode sheet prepared in Example 1 at 0% SOC and 100% SOC, T' 0% SOC 63μm( Figure 2 c), T' 100%SOC 70μm( Figure 2 c'). It can be seen that the average thickness increase rate of the negative electrode coated with the first active layer and the second active layer alone is almost the same as the thickness increase rate of the double-layer negative electrode in Example 1. This shows that the results obtained by the above separate tests are reliable.
[0109] Testing battery performance
[0110] (1) Charging rate test
[0111] The battery cell was constant capacity obtained to obtain the capacity Q0, constant capacity conditions: the battery cell was allowed to stand at 25°C for 30 min, discharged at 0.33C to 2.0V, charged at 0.33C constant current to 3.65V, charged at constant voltage with a cutoff current of 0.05C, and discharged at 0.33C to 2.0V to obtain the capacity Q0.
[0112] With Q0 as 100% SOC, within the range of 0 to 80% SOC, at every 5% SOC, let I5 be the charging current from 0 to 5% SOC, I 10 is the charging current of 5~10% SOC, and so on; let C5 be the charging rate of 0~5% SOC, C5=I5 / Q0; C 10 The charge rate is 5~10% SOC, C 10 =I 10 / Q0, and so on. Adjust C5~C 80 The value is used to minimize the charging time of the battery cell without lithium deposition at 0-80% SOC, denoted by C. QC=2880 / (180 / C5+180 / C 10 +…+180 / C 80 ) is 0~80% SOC equivalent multiple. The test results are shown in Table 2.
[0113] (2) Volume energy density test
[0114] The battery cell was constant-capacity to obtain energy E0, and the constant-capacity conditions were as follows: the battery cell was allowed to stand at 25°C for 30 min, discharged at 0.33C to 2.0V, charged at 0.33C constant current to 3.65V, charged at constant voltage with a cut-off current of 0.05C, and discharged at 0.33C to 2.0V to obtain capacity E0.
[0115] Measure the length, width and height of the fully charged battery cell and record them as L, W and h, and multiply them to get the cell volume V 100 , volume energy density is recorded as VED0 = E0 / V 100 The test results are shown in Table 2.
[0116] (3) Cycle life test
[0117] The battery cell was constant capacity obtained to obtain the capacity Q0, constant capacity conditions: the battery cell was allowed to stand at 25°C for 30 min, discharged at 0.33C to 2.0V, charged at 0.33C constant current to 3.65V, charged at constant voltage with a cutoff current of 0.05C, and discharged at 0.33C to 2.0V to obtain the capacity Q0.
[0118] The battery cell was left to stand at 25℃ for 30min and the charge rate was tested according to the C x According to the definition of Table 1 below, charge the battery to 80% SOC.
[0119] Table 1
[0120]
[0121]
[0122] Continue to charge the battery to full power, 0.33C constant current charge to 3.65V, constant voltage charge, cut-off current 0.05C, 1C discharge to 2.0V, and cycle this process. The test ends when the capacity decays to 80% Q0. The test results are shown in Table 2. The cycle performance comparison of Examples 1-3 and Comparative Examples 1-3 is shown in Figure 3 shown.
[0123] (4) Calculation of the change in the amount of liquid absorbed by the first active layer
[0124] The calculation of the change in liquid absorption is carried out simultaneously with the thickening rate test. The thickness T' in the calculation formula 0%SOC and T' 100%SOCis the result measured in the thickening rate test in (1) above, T' 0%SOC is the thickness of the first active layer at 0% charge state, T' 100%SOC is the thickness of the first active layer at 100% charge state, in μm; the true density of each component is ρ' Gr (Gr represents graphite), ρ' SP , ρ' CMC , ρ' PAA , ρ' SBR , the mass ratio of each component in the negative electrode coating is w' Gr %、w' SP %、w' CMC %、w' PAA %、w' SBR %. The density of the first active surface is m', in g / m 2 ;
[0125] When SOC is 0%, the porosity is v'0 =
[0126] (w' Gr %*m' / ρ' Gr +w' SP %*m' / ρ' SP +w' CMC %*m' / ρ' CMC +w' PAA %*m' / ρ' PAA +w' SBR %*m' / ρ' SBR ) / T' 0% SOC
[0127] The porosity at 100% SOC is v' 100 =
[0128] (w' Gr %*m' / ρ' Gr +w' SP %*m' / ρ' SP +w' CMC %*m' / ρ' CMC +w' PAA %*m' / ρ' PAA +w' SBR %*m' / ρ' SBR ) / T' 100 %SOC.
[0129] The electrolyte density is 1.2 g / mL, and the first active layer absorbs 1.2*(v' 100 The test results are shown in Table 2.
[0130] (5) Calculation of the change in the liquid absorption of the second active layer
[0131] The calculation of the change in liquid absorption is carried out simultaneously with the thickening rate test. The thickness T" in the calculation formula 0%SOC and T” 100%SOC is the result measured in the thickening rate test in (1) above, T” 0%SOC is the thickness of the second active layer at 0% charge state, T” 100%SOC is the thickness of the second active layer at 100% charge state, in μm; the true density of each component is ρ” Gr ,ρ” SP ,ρ” CMC ,ρ” PAA ,ρ” SBR , unit: g / cm 3 , the mass ratio of each component in the negative electrode coating is w" Gr %、w” SP %、w” CMC %、w” PAA %、w” SBR %, the density of the second active surface is m", unit: g / m 2 ;
[0132] The porosity at 0% SOC is v"0 =
[0133] (w” Gr %*m” / ρ” Gr +w" SP %*m” / ρ” SP +w" CMC %*m” / ρ” CMC +w" PAA %*m” / ρ” PAA +w" SBR %*m” / ρ” SBR ) / T” 0%SOC
[0134] The porosity at 100% SOC is v" 100 =
[0135] (w” Gr %*m” / ρ” G +w" SP %*m” / ρ” SP +w" CMC %*m” / ρ” CMC +w" PAA %*m” / ρ” PAA +w" SBR %*m” / ρ” SBR ) / T” 100%SOC .
[0136] The electrolyte density is 1.2g / mL, and the second active layer absorbs 1.2*(v” 100 The test results are shown in Table 2.
[0137] Table 2
[0138]
[0139] By comparing the embodiments and the comparative examples, it can be seen that by coating active layers with different thickening rates on the negative electrode current collector, and controlling the thickening rate of the active layer to decrease successively from the direction close to the negative electrode current collector to the direction away from the negative electrode current collector, and controlling the thickening rate of the first active layer to be above 12%, and the thickening rates of the second active layer to the nth active layer to be below 12%, the negative electrode sheet obtains a smaller thickness change and porosity change in the upper active layer during charging, thereby ensuring the energy density of the battery; at the same time, the lower active layer obtains a larger thickness change and porosity change, resulting in absorption of the electrolyte, and utilizing the convective mass transfer of the electrolyte to reduce the Li in the inner layer of the electrode dressing. + The diffusion polarization of the battery can be reduced, thereby improving the battery's charging rate and cycle life while ensuring the battery's energy density and capacity.
[0140] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0141] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A negative electrode plate, characterized in that: The invention comprises a negative electrode current collector and a negative electrode coating disposed on at least one side of the negative electrode current collector, wherein the negative electrode coating comprises: a first active layer close to the negative electrode current collector, a second active layer disposed on the first active layer, and so on, an nth active layer disposed on the n-1th active layer, where n is an integer from 2 to 5; and the negative electrode active material in each active layer is graphite; The thickness increase rate ΔT of the active layer decreases from the first active layer to the nth active layer, ΔT=(T 100%SOC -T 0%SOC )÷T 0%SOC , T 100%SOC Indicates the thickness of the active layer at 100% charge state, T 0%SOC represents the thickness of the active layer in the 0% charged state; and the thickness increase rate of the first active layer is greater than 12%, and the thickness increase rates of the second active layer to the nth active layer are all less than 12%.
2. The negative electrode sheet according to claim 1, characterized in that: n is 2, the thickness increase rate ΔT' of the first active layer is greater than the thickness increase rate ΔT' of the second active layer ΔT'=(T' 100%SOC -T' 0%SOC )÷T' 0%SOC , T' 100%SOC represents the thickness of the first active layer at 100% charge state, T' 0%SOC represents the thickness of the first active layer at 0% charge state; ΔT”=(T” 100%SOC -T" 0%SOC )÷T” 0%SOC , T” 100%SOC represents the thickness of the second active layer at 100% charge state, T” 0%SOC represents the thickness of the second active layer at 0% charge state.
3. The negative electrode sheet according to claim 2, characterized in that: The thickness increase rate of the first active layer is 12% to 18%, and the thickness increase rate of the second active layer is 6% to 12%; Preferably, the thickness increase rate ΔT' of the first active layer is 15% to 18%; the thickness increase rate ΔT" of the second active layer is 6% to 10%.
4. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: The raw materials of the first active layer include a first dispersant and a first binder, the raw materials of the second active layer include a second dispersant and a second binder, and so on, the raw materials of the nth active layer include an nth dispersant and an nth binder; the elastic modulus of the film formed by the first dispersant and the first binder is smaller than the elastic modulus of the film formed by the second dispersant and the second binder; and so on, the elastic modulus of the film formed by the n-1th dispersant and the n-1th binder is smaller than the elastic modulus of the film formed by the nth dispersant and the nth binder.
5. The negative electrode sheet according to claim 4, characterized in that: The mass ratio of the first dispersant to the first binder is (0.1-1.2):(1.8-3.8); the total mass proportion of the first dispersant and the first binder in the raw material of the first active layer is 1.9%-5.0%; the elastic modulus of the film formed by the first dispersant and the first binder is 10MPa-50MPa; The mass ratio of the second dispersant and the second binder is (0.3-1.4):(0.2-2.3); the mass proportion of the second dispersant and the second binder in the raw materials of the second active layer is 0.5%-3.7%; the elastic modulus of the film formed by the second dispersant and the second binder is 55MPa-100MPa.
6. The negative electrode sheet according to claim 5, characterized in that: The mass ratio of the first dispersant to the first binder is (1-1.2):(2-3); the total mass proportion of the first dispersant and the first binder in the raw material of the first active layer is 3%-4.2%; the elastic modulus of the film formed by the first dispersant and the first binder is 10MPa-20MPa; The mass ratio of the second dispersant and the second binder is (0.3-0.7):(1.3-2.3); the mass proportion of the second dispersant and the second binder in the raw materials of the second active layer is 1.6%-3.0%; the elastic modulus of the film formed by the second dispersant and the second binder is 60MPa-80MPa.
7. The negative electrode sheet according to claim 4, characterized in that: The first binder, the second binder, and so on to the nth binder each include one or more of styrene-butadiene rubber, polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol, sodium alginate, polymethacrylic acid and carboxymethyl chitosan; The first dispersant, the second dispersant, and so on to the nth dispersant each include one or more of sodium carboxymethyl cellulose and lithium carboxymethyl cellulose.
8. The negative electrode sheet according to any one of claims 1 to 3, characterized in that: n is 2, and the raw materials of the first active layer include graphite, a first conductive agent, a first dispersant, and a first binder; the mass ratio of graphite, the first conductive agent, the first dispersant, and the first binder is (93.4-97.4):(0.3-1.6):(0.1-1.2):(1.8-3.8); The raw materials of the second active layer include graphite, a second conductive agent, a second dispersant and a second binder; the mass ratio of graphite, the second conductive agent, the second dispersant and the second binder is (96.6-98.9):(0-0.8):(0.3-1.4):(0.2-2.3).
9. A battery, characterized in that: A negative electrode sheet comprising any one of claims 1 to 8.
10. An electrical device, characterized in that: A battery comprising the battery of claim 9.